2014
DOI: 10.5430/jnep.v5n2p89
|View full text |Cite
|
Sign up to set email alerts
|

Talking about weight in pregnancy: An exploration of practitioners' and women's perceptions

Abstract: Prevalence of maternal obesity is increasing, with health risks for mother and infant. Effective health promotion depends on sufficient knowledge and appropriate communication skills. We aimed to explore women's, midwives' and health visitors' perceptions of current practice in helping women manage their weight and supporting healthy behaviour change during pregnancy, and their perceived training needs. A modified grounded theory methodology was adopted, based upon critical realist assumptions. Following consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Participants were tentative about raising the issue of weight with women who are overweight, through fears of compromising their relationship and jeopardising future attendance, which is also a finding reported elsewhere in the maternal obesity literature (e.g. Furness et al, 2015). McCourt (2006) found that midwives have tended to adopt hierarchical and conventional styles of communication at the booking appointment (McCourt, 2006).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Participants were tentative about raising the issue of weight with women who are overweight, through fears of compromising their relationship and jeopardising future attendance, which is also a finding reported elsewhere in the maternal obesity literature (e.g. Furness et al, 2015). McCourt (2006) found that midwives have tended to adopt hierarchical and conventional styles of communication at the booking appointment (McCourt, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…However, there was an acceptance that in the postpartum period they would revert back to the healthier lifestyle they lead prepregnancy. Therefore, intervening postpartum might prove a more opportune time for WO to change their weight-related behaviours, which has been reported previously Furness et al, 2015;Atkinson, Olander & French, 2016). Many HCP's have proposed the pre-pregnancy period as the time to intervene, rendering pregnancy 'too late' to change (Heslehurst et al, 2007).…”
Section: Women's Perspectives On Leading a Healthy Lifestyle During Pmentioning
confidence: 72%
See 1 more Smart Citation
“…[ 4 5 6 ] The consumption of fast food and soft drinks, excessive sugar intake, and lack of consumption of fruits, vegetables, and food with high fiber content are consequences of the nutrition transition that have affected all social classes including women. [ 7 8 ] A study showed that the diet of 73% of Iranians require modification. [ 9 ] Moreover, 63.90% of Iranian women are overweight or obese, 35% of which gain more weight than recommended during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Various interventions have been implemented for weight management and nutritional modification during pregnancy, but their results have not presented long-term effects. [ 7 ] Researchers' lack of consideration of psychological issues related to nutritional behavior has been reported as one of the main reasons for the lack of success of interventions and education in this regard. [ 11 ] In many studies, specialists in this field have emphasized on appropriate goal determination for the most important individual, social, and environmental factors in order to improve health behavior such as nutritional habits.…”
Section: Introductionmentioning
confidence: 99%